2004
DOI: 10.1051/0004-6361:20034046
|View full text |Cite
|
Sign up to set email alerts
|

The influence of density stratification and multiple nonlinearities on solar torsional oscillations

Abstract: Abstract. Analyses of recent helioseismic data have produced ample evidence for substantial dynamical variation of the differential rotation within the solar convection zone. Given the inevitable difficulties in resolving the precise nature of variations in deeper layers, much effort has recently gone into determining theoretically the expected modes of behaviour, using nonlinear dynamo models. Two important limitations of these models are that they have so far included only one form of nonlinearity, and as ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…This parallels our previous studies of solar torsional oscillations (see, e.g., Covas et al 2000;Tavakol et al 2002;Covas et al 2004, and references therein). We investigate the nature of variations in the convection zones of rapidly rotating stars, by considering three families of models with different depths of dynamo-active regions ("convective envelopes").…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This parallels our previous studies of solar torsional oscillations (see, e.g., Covas et al 2000;Tavakol et al 2002;Covas et al 2004, and references therein). We investigate the nature of variations in the convection zones of rapidly rotating stars, by considering three families of models with different depths of dynamo-active regions ("convective envelopes").…”
Section: Introductionsupporting
confidence: 91%
“…Throughout we take α r > 0 and R α < 0 and use a uniform density: our earlier work (Covas et al 2004) illustrates the effects of introducing a strongly radially dependent density -in brief, no qualitatively new effects are found, although the radial distribution of perturbations to the angular velocity can be altered. In particular, it tends to increase (decrease) the strength of the torsional oscillations at the top (bottom) of the convection zone.…”
Section: The Modelmentioning
confidence: 99%
“…The amplitude of the oscillations is up to 5% of the angular velocity, i.e., a few times larger than the observed ones. In a turbulent mean-field model, where the magnetic feedback is mediated solely by the Lorentz force, Covas et al (2004) found that the amplitude of the oscillations depends on the amplitude of the α-effect. It is possible to verify this finding in global simulations by varying the Rossby number.…”
Section: Understanding Torsional Oscillationsmentioning
confidence: 99%
“…It is puzzling that the equatorward branch starts before the beginning of the magnetic cycle. The magnetic feedback via the Lorentz force on the plasma flow is one possible explanation motivated by mean-field turbulent dynamo models (Yoshimura 1981;Kleeorin & Ruzmaikin 1981;Covas et al 2000Covas et al , 2004. In a flux-transport dynamo model, where the source of the poloidal field is non-local and depends on the buoyancy of magnetic flux tubes, Rempel (2007) explained the high latitude branch of the oscillations as a result of the magnetic forcing, while arguing that the equatorial branch has a thermal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Candidates for the driving mechanism are Lorentz force feedback (e.g., Schüssler 1981;Yoshimura 1981), thermal feedback (Spruit 2003), and magnetic quenching of turbulent angular momentum transport (Kitchatinov & Pipin 1998;Kitchatinov et al 1999). Most models of torsional oscillations to date are based on Lorentz force feedback, most of them use a simplified momentum equation only considering zonal flows (see, e.g., Covas et al 2000Covas et al , 2004Covas et al , 2005Chakraborty et al 2009aChakraborty et al , 2009b. While this approach allows for quite realistic torsional oscillations there are two major problems.…”
Section: Introductionmentioning
confidence: 99%